Speaking rate and articulation rate of native speakers of Irish English. (2nd October 2017) - Lee, Alice; Doherty, Rachel
ABSTRACT: Previous studies have shown apparent difference in speaking rate and/or articulation rate between different dialects of English. In addition, native speakers of Irish English are perceived to be speaking very fast; however, there is very little information in the current literature regarding speech rate of speakers of this variety of English. Establishing regional norms might be needed for various reasons, such as speech intervention, if speakers of Irish English do have a higher speaking and articulation rates than individuals who speaks other English dialects. This study measured the speaking rate and articulation rate of 22 men and 22 women who were native speakers of Irish English. The study compared the speech rates between the male and female speakers, and across different speech tasks – first and second reading of the Rainbow Passage and spontaneous speech elicited in a conversation. Overall, the male speakers seemed to speak faster than the females, although significant difference was found only in the articulation rate for the second reading of the passage. The speakers showed significantly higher speaking rate during passage reading than in conversation but the difference in articulation rate between the two tasks was not significant. Finally, the Irish English speakers in this study appeared to have relatively higher speech rates than most of the English dialects reported in previous studies.